Psychological contract and organizational change in a company belonging to a tertiary sector in the of city Bogotá, Colombia (2015)
The general objective of this research was to determine the relationship between psychological contract and the willingness to accept an organizational change in the employees of a company in the city of Bogota. So, two evaluation instruments were used: The organizational change measurement instrument (BMI) (García &amp, Forero, 2010) and the inventory of psychological contract (Rousseau, 2000 version 2): For this, two assessment tools were used. The sample was made up of 100 employees and their participation was voluntary. The description and analysis of the results were performed by using the SPSS Statistics 20 software. The assessment of the normal distribution of subvariables research was performed by using the statistical test Kolmogorov - Smirnov and to determine the levels and significance between variables and subvariables, the Spearman correlation coefficient in consideration of the scale of measurement was used. Evidences of correlation between the variables of organizational change and psychological contract were noticed. It is concluded that the employees of the company show a willingness of flexibility and favorability versus an organizational change.